Effects of a Total Motion Release (TMR®) Protocol for the Single Leg Squat on Asymmetrical Movement Patterns - Nickolai JP Martonick; Craig P McGowan; Russell T Baker; Lindsay W Larkins; Jeff G Seegmiller; Joshua P Bailey (International Journal of Sports Physical Therapy)
# BACKGROUND